Tinjauan Al-Quran Dan Hadis Terhadap Pendidikan Anti Kekerasan (Analisis Interaksi Pewahyuan Jibril, Muhammad Dan Sahabat) - Sirojul Munir, Moh; Hamid Hafid, Abdul; Shobri Alwi, Alwi (Mu'allim, 2024)
Cases of violence in the educational environment are a major concern that has not been resolved by many parties. Women and Child Protection (SIMFONIPPA) recorded 1,993 cases of child abuse during the period January to February 2024, with the majority of large cases occurring in educational environments labeled as Islamic. This article analyzes the essence of harmonious education championed by the Prophet Muhammad, starting from the revelation process by the Angel Gabriel to the interaction with the Companions in delivering Islamic sharia education. Understanding the shifting paradigm of the meaning of violence is also the main focus of this research, as an effort to provide a deeper understanding of the meaning of violence in the Prophet's time and modern times. The research method used is library research with a descriptive qualitative approach. The results show differences in the definition of the concept of violence in the Prophet's time and modern times according to different contexts of social interaction. Lack of understanding of Islamic sources is the main cause why the understanding of violence in the Prophet's time has not been applied effectively in modern times.